The administration of intraperitoneal prilocaine for postoperative analgesia after laparoscopy [LAPAROSKOPI SONRASI ANALJEZI AMACI ILE INTRAPERITONEAL PRILOKAIN UYGULANMASI] - (:unkn) unknown (My University, 1995)
Laparoscopy has been widely used for both diagnostic and operative gynecologic purposes for outpatients. Postoperative pain caused by stretched diaphragm is a common complication which delay mobilisation of the patients. The aim of this prospective, randomized study is to evaluate the effectiveness and the side effects of 10 ml 2 % prilocaine applied intraperitoneally for the control of postoperative pain of outpatients scheduled for diagnostic laparoscopy. 24 outpatients whose average age were 30.21 were randomly assigned to two groups as receiving 10 ml 2% prilocaine (n=12) or 10 ml % 0.9 physiological saline (n=12) intraperitoneally at the end of laparoscopy. Pain was assessed using visual analogue scale at 1, 2, and 4 hours postoperatively. 50 mg Meperidine hydrochloride was used intravenously as an analgesic for all patients at the end of first hour postoperatively. In the prilocaine treated group visual analogue scale scores were significantly lower than the control (Placebo) group at postoperative 1, 2 and 4 hours (p<0.001, p<0.01, p<0.05). As a result, we concluded that the administration of 10 ml 2% prilocaine intraperitoneally, at the end of laparoscopy is an effective, safe and simple method for the control of immediate postoperative pain of outpatients scheduled for diagnostic laparoscopy.
Keywords: Intraperitoneal anesthesia; Laparoscopy; Postoperative analgesia; Prilocaine